The Role of NGAL in Peritoneal Dialysis Effluent in Early Diagnosis of Peritonitis: Case-Control Study in Peritoneal Dialysis Patients - Martino, Francesca (Perit Dial Int, 2015)
♦ BACKGROUND: Peritoneal dialysis (PD) is frequently complicated by high rates of peritonitis, which result in hospitalization, technique failure, transfer to hemodialysis, and increased mortality. Early diagnosis, and identification of contributing factors are essential components to increasing effectiveness of care. In previous reports, neutrophil gelatinase-associated lipocalin (NGAL), a lipocalin which is a key player in innate immunity and rapidly detectable in peritoneal dialysis effluent (PDE), has been demonstrated to be a useful tool in the early diagnosis of peritonitis. This study investigates predictive value of PDE NGAL concentration as a prognostic indicator for PD-related peritonitis. ♦ METHODS: A case-control study with 182 PD patients was conducted. Plasma and PDE were analyzed for the following biomarkers: C-reactive protein (CRP), blood procalcitonin (PCT), leucocytes and NGAL in PDE. The cases consisted of patients with suspected peritonitis, while controls were the patients who came to our ambulatory clinic for routine visits without any sign of peritonitis. The episodes of peritonitis were defined in agreement with International Society for Peritoneal Dialysis guidelines. Continuous variables were presented as the median values and interquartile range (IQR). Mann-Whitney U test was used to compare continuous variables. Univariate and multivariate logistic regression were used to evaluate the association of biomarkers with peritonitis. Receiver operating characteristic (ROC) curve analysis was used to calculate area under curve (AUC) for biomarkers. Finally we evaluated sensitivity, and specificity for each biomarker. All statistical analyses were performed with SPSS version 17.0 (SPSS Inc., Chicago, IL, USA). ♦ RESULTS: During the 19-month study, of the 182 patients, 80 had a clinical diagnosis of peritonitis. C-reactive protein levels (p < 0.001), PCT (p < 0.001), NGAL in PDE (p < 0.001), and white blood cells (WBC) in PDE (p < 0.001) were all significantly different in patients with and without peritonitis. In univariate analysis, CRP (odds ratio [OR] 1,339; p = 0.001), PCT (OR 2,473; p < 0,001), WBC in PDE (OR 3,986; p < 0,001), and NGAL in PDE (OR 36.75 p < 0.001) were significantly associated with episodes of peritonitis. In multivariate regression analysis, only WBC (OR 24.84; p = 0,012), and peritoneal NGAL levels (OR 136.6; p = 0,01) were independent predictors of peritonitis events. Moreover, AUC for NGAL in peritoneal effluent was 0,936 (p < 0.001) while AUC for CRP, PCT, and WBC count in peritoneal effluent were 0,704 (p = 0.001), 0.762 (p = 0.039), 0,975 (p < 0.001), respectively. Finally, combined WBC and peritoneal NGAL test increased the specificity (= 96%) of the single test. ♦ CONCLUSIONS: These results identify NGAL in peritoneal effluent as a reliable marker of peritonitis episodes in PD patients. Collectively, our findings demonstrate that the use of peritoneal NGAL cooperatively with current clinical diagnostic tools as a prognostic indicator, presents a valuable diagnostic tool in PD-associated peritonitis.